Charlie and the great glass elevator [compact disc, unabridged] - Dahl, Roald (Penguin Audio, 2013)
In this follow-up to the tremendously popular Charlie and the Chocolate Factory, Willy Wonka tells the Bucket family of his plans to give Charlie his entire candy empire. Reluctantly joining Wonka on a ride in the Glass Elevator, the Buckets embark on a wild adventure when a mistake skyrockets the vessel into space. Now, Wonka, Charlie, Grandpa Joe, and the rest of the family must fight off Vermicious Knids if they are to make it home in one piece.